2018
DOI: 10.1016/j.alit.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum periostin is associated with body mass index and allergic rhinitis in healthy and asthmatic subjects

Abstract: Our results provided clarity as to the factors associated with serum periostin levels, which could be helpful in the interpretation of serum periostin levels in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
4
17
1
1
Order By: Relevance
“…The median (interquartile range [IQR]) periostin level was 50.1 (43.1 to 56.9) ng/ml, with a five-fold range of 28.1 to 136.4 ng/ml, and the 90% confidence limits were 35.0 to 71.1 ng/ml. There was no association between serum periostin levels and age, sex or common non-respiratory comorbidities, but serum periostin levels were lower in current smokers and lower in those with a high body mass index (BMI), consistent with other studies [40][41][42] . A related study showed a modest reduction in serum periostin levels in the evening, compared with morning testing (46.2 ng/ml at 1800 hr versus 50.5 ng/ml at 0800 hr) 43 .…”
Section: What Is Known About Periostinsupporting
confidence: 88%
See 1 more Smart Citation
“…The median (interquartile range [IQR]) periostin level was 50.1 (43.1 to 56.9) ng/ml, with a five-fold range of 28.1 to 136.4 ng/ml, and the 90% confidence limits were 35.0 to 71.1 ng/ml. There was no association between serum periostin levels and age, sex or common non-respiratory comorbidities, but serum periostin levels were lower in current smokers and lower in those with a high body mass index (BMI), consistent with other studies [40][41][42] . A related study showed a modest reduction in serum periostin levels in the evening, compared with morning testing (46.2 ng/ml at 1800 hr versus 50.5 ng/ml at 0800 hr) 43 .…”
Section: What Is Known About Periostinsupporting
confidence: 88%
“…Allergic rhinitis in non-asthmatics, but not in asthmatics, is associated with higher periostin levels 42 . Periostin has been implicated in the inflammatory and fibrotic pathways of atopic dermatitis 50 , psoriasis 51 and chronic rhino-sinusitis with nasal polyps 52,53 .…”
Section: Influence Of Type-2 Inflammatory Related Conditionsmentioning
confidence: 99%
“…Class I obese participants showed higher POSTN plasma levels in comparison to overweight and class II-III obese patients, who exhibited the lowest POSTN plasma level. There was a controversial view in the literature where some studies have shown that BMI is in a negative association with serum POSTN in both healthy and asthmatic subjects, 43,44 while others showed that there is no significant correlation between BMI and serum POSTN level. 45 Due to the direct anatomic relation between the mouth and the upper airways and their similarity in cytokine composition with the lower airways in asthma, salivary analysis of POSTN could offer noninvasive rapid diagnostic aid in asthma control deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…The level of serum POSTN in healthy controls averages 66.1 ng/mL, as reported by Kimura et al . 42 . The JESREC score used in the present study is calculated based on unilateral or bilateral disease, the presence of NPs, the dominant shadow of ethmoid sinuses in CT scans, and the eosinophil ratio in peripheral blood 7 .…”
Section: Discussionmentioning
confidence: 99%